An exploration on the use of realia-mediated instruction for teaching English for young learners - Sarfita Br Sitepu; Lemmuela Alvita Kurniawati (Research And Innovation In Language Learning (RILL), 2021)
This study aims to investigate how teachers and young learners use realia in a private English course in the Indonesian context and to explore the viewpoints of teachers on using realia for young learners learning English. To gather the data, this study employed a qualitative research method with interpretivism paradigm. Three English teachers in a private English course involved in this study. To gain rich data, interviews with three English teachers and observations in Kids classes were conducted. Two themes emerged for research question 1 were realia is used to teach vocabulary and realia is used to assess students understanding. Three emerging themes for research question 2 were realia helps students engaged in learning process, realia helps students maximize their multi-sensory English learning experience, and realia increases students communication skill. Implications and recommendations were provided and further elaborated based on the results of the study.